2014
DOI: 10.1371/journal.pone.0102699
|View full text |Cite
|
Sign up to set email alerts
|

The Anabolic Androgenic Steroid Nandrolone Decanoate Disrupts Redox Homeostasis in Liver, Heart and Kidney of Male Wistar Rats

Abstract: The abuse of anabolic androgenic steroids (AAS) may cause side effects in several tissues. Oxidative stress is linked to the pathophysiology of most of these alterations, being involved in fibrosis, cellular proliferation, tumorigenesis, amongst others. Thus, the aim of this study was to determine the impact of supraphysiological doses of nandrolone decanoate (DECA) on the redox balance of liver, heart and kidney. Wistar male rats were treated with intramuscular injections of vehicle or DECA (1 mg.100 g−1 body… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(44 citation statements)
references
References 30 publications
5
35
1
3
Order By: Relevance
“…This significant increase in hepatic antioxidants activity in the Su -treated groups is in harmony with Pey et al who observed that abuse of AAS for 8 weeks, either with or without concurrent exercise training, causes an increase the activities of the antioxidant enzymes in hepatic tissue as compared with control group [7]. On the contrary, Frankenfeld et al reported that the abuse of AAS decreases the liver antioxidants activity [20].…”
Section: Alt (Iu/l) Ast (Iu/l) Alp (Iu/l)supporting
confidence: 81%
“…This significant increase in hepatic antioxidants activity in the Su -treated groups is in harmony with Pey et al who observed that abuse of AAS for 8 weeks, either with or without concurrent exercise training, causes an increase the activities of the antioxidant enzymes in hepatic tissue as compared with control group [7]. On the contrary, Frankenfeld et al reported that the abuse of AAS decreases the liver antioxidants activity [20].…”
Section: Alt (Iu/l) Ast (Iu/l) Alp (Iu/l)supporting
confidence: 81%
“…Experimental studies have demonstrated that chronic administration of AS can up-regulate the activity of NOX in several cell types, resulting in increased ROS production, whereas antioxidant activity seems to be substantially decreased in this condition [63,94]. In the CNS, chronic administration of nandrolone decanoate in rats has been shown to decrease glutathione peroxidase (Gpx) activity in the hippocampus and pre-frontal cortex [79].…”
Section: Redox Imbalancementioning
confidence: 99%
“…These renal abnormalities could be a consequence of oxidative stress caused by AAS use, which involves fibrosis, cellular proliferation, cytokine release and other substances that in turn allow the increase of some biomarkers, including MCP-1 and KIM-1, making it possible to detect early kidney damage (23).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%